БУХОРО ТУМАНИ ТОПОНИМЛАРИНИНГ ТАСНИФИ - Адизова, Н. (SCIENCE and SOCIETY, 2020)
In the article toponyms of Bukhara region are classified into thematic groups and analyzed from diachronic and synchronous approaches.